Degradation of Gaseous Formaldehyde by Visible Light-Responsive Titania Photocatalyst Filter - Tun-Ping Teng; Tun-Chien Teng; Shu-I Pan (International Journal of Photoenergy)
A method is proposed that uses electrophoretic deposition (EPD) to fabricate the titania (TiO2) photocatalyst filter and then successfully modifies it by lithium nitrate (LiNO3) to be visible light responsive such that the modified photocatalyst filter effectively degrades gaseous formaldehyde. The performance of degrading gaseous formaldehyde is evaluated in the photocatalytic circulation reactor for different temperature and light sources. The results show that the modified TiO2 photocatalyst filter has much better degradation performance for gaseous formaldehyde than the original TiO2 photocatalyst filter regardless of light source, and the performance is better at the higher ambient temperature. The best total average degradation performance of the modified photocatalyst filter is about 9.2% and 16.3% higher than the original photocatalyst filter (P-25, Degussa) for the UVA and visible irradiation, respectively, at 26°C.